Pengaruh Pembelajaran Responsi Pra Praktikum dan Jobsheet Terpadu Terhadap Hasil Belajar Mahasiswa pada Praktik Pengukuran Listrik - Amin, Muhammad (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
The objective of the study was to determine the differences of learning outcomes between the students treated with pre-practice review session and the students treated with integrated job sheets in the course of Electrical Measurement Practices. This study is categorized as a quasi experimental study. The data analysis technique used two-ways analysis of variance (Anova) and the credibility level of 0.05. The results showed that (1) There were differences of learning outcomes between the group treated with pre-practice review session ( =81,35) and the  group treated with integrated job sheets ( =76,04); (2) There were differences in learning outcomes between the group having low entry behaviour ( =81,35) with the group having high entry behaviour ( =71,00); (3) There was no interaction between the students’ entry behaviour with the pattern of the improvement (4) The experimental group treated with pre-practicum review session for the students having high entry behaviour showed the best learning outcomes